On quotient clean hyperring - S. Ostadhadi-Dehkord (Journal of Hyperstructures)
In this paper, we introduce the notion of quotient Krasner hyperrings and prove that if I is a normal ideal of Krasner hyperring (R, +, ·), then quotient clean Krasner hyperring considered in [1] by Talebi et. al are just clean rings.